2019
DOI: 10.1186/s12881-019-0880-1
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colorectal cancer and severe hypocalcemia following irinotecan administration in a patient with X-linked agammaglobulinemia: a case report

Abstract: Background X-linked agammaglobulinemia (XLA) is a primary immunodeficiency disorder caused by germline mutations in the Bruton tyrosine kinase (BTK) gene on X chromosome. These mutations disturb B-cell development, decrease immunoglobulin levels, increase susceptibility to infection or neoplasms, and increase the risk of developing colorectal cancer (CRC). For occasional cases of CRC have been reported in XLA patients, low levels of B lymphocytes and immunoglobulins induced by congenital immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Our results showed that CD36 was significantly downregulated in CRC tissues compared to normal tissues, which was validated in vitro and in vivo [ 26 ]. Genome-wide DNA methylation analysis revealed that hypermethylation of CD36 could contribute to its low expression [ 27 ]. Fang et al found that CD36 expression gradually decreased from adenoma to cancer and CD36 loss implied a poor prognosis in patients with CRC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that CD36 was significantly downregulated in CRC tissues compared to normal tissues, which was validated in vitro and in vivo [ 26 ]. Genome-wide DNA methylation analysis revealed that hypermethylation of CD36 could contribute to its low expression [ 27 ]. Fang et al found that CD36 expression gradually decreased from adenoma to cancer and CD36 loss implied a poor prognosis in patients with CRC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting genomic rearrangements originating at G4-motifs may lead to secondary cancer development greatly complicating patient treatment. Other studies have documented secondary cancer development in patients following treatment with CPT-derivatives [ 68 , 69 ]. In the future, it will be valuable to explore how CPT-treatment and subsequent emergence of Top1 mutants can lead to further genome instability and potential secondary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…At present, TDM is being performed to elucidate the pharmacokinetic properties of drugs. However, there are some case reports of dose adjustment of 5-FU prodrugs by TDM (Table II) (48)(49)(50)(51)(52). Tanaka reported that TDM of S-1 was used in patients with recurrent gastric cancer undergoing maintenance dialysis to estimate the appropriate S-1 dose and administer treatment.…”
Section: Individualized Treatment With Tdm Of 5-fu and 5-fu Prodrugsmentioning
confidence: 99%
“…Yoshida performed TDM of capecitabine in a colon cancer patient with DPD deficiency, and the dose was adjusted while observing side effects (51). Li reported that TDM of capecitabine was performed in immunodeficient X-linked agammaglobulinaemia colorectal cancer patients, and the dose was adjusted while focusing on the appearance of toxicity (52).…”
Section: Individualized Treatment With Tdm Of 5-fu and 5-fu Prodrugsmentioning
confidence: 99%